2011
DOI: 10.2527/jas.2010-3756
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the use of supplemental amino acids in corn-soybean meal diets for 20- to 45-kilogram pigs1,2

Abstract: Four experiments were conducted to determine the Lys requirement, the maximum amount of supplemental Lys that does not decrease growth performance, and to determine the order of limiting AA beyond Lys, Thr, Trp, and Met in a corn-soybean meal diet for 20- to 45-kg pigs. All experiments were conducted for 27 to 28 d with purebred or crossbred barrows and gilts, which were blocked by initial BW. Treatments were replicated with 4 to 6 pens of 4 to 6 pigs per pen. In all experiments, pigs and feeders were weighed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Dietary treatments did not affect ADFI, indicating that Lys source or concentration did not affect feed intake. This is in agreement with the results of Roux et al (2011), who reported that ADFI was not affected by supplemental Lys addition from a crystalline source in diets fed to 20-to 45-kg pigs. Lopez et al (1994) evaluated a group of gilts from 71 to 102 kg in a thermoneutral environment and fed control and ideal diets, in which Lys concentration was limiting (0.65%), and reported that ADFI was not different for gilts fed the intact diet compared with gilts fed the ideal protein diet.…”
Section: Discussionsupporting
confidence: 93%
“…Dietary treatments did not affect ADFI, indicating that Lys source or concentration did not affect feed intake. This is in agreement with the results of Roux et al (2011), who reported that ADFI was not affected by supplemental Lys addition from a crystalline source in diets fed to 20-to 45-kg pigs. Lopez et al (1994) evaluated a group of gilts from 71 to 102 kg in a thermoneutral environment and fed control and ideal diets, in which Lys concentration was limiting (0.65%), and reported that ADFI was not different for gilts fed the intact diet compared with gilts fed the ideal protein diet.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies within our research group have shown that grower pigs (20 to 50 kg) fed a low-CP diet supplemented with 0.34% Lys along with Thr, Met, and Trp had reduced growth performance compared with pigs fed a positive control (PC) diet with no supplemental AA (Roux et al, 2011). Growth performance was improved with the supplementation of He and Val; however, G:F was less than that of pigs fed the PC.…”
Section: Introductionmentioning
confidence: 44%
“…To achieve a Met:Cys of 50:50, L-Cys was supplemented to the diet to replace dietary Met. The quantity of Gly supplemented was done to achieve 1.35% Gly -I-Ser, which has been reported previously to provide growth performance similar to that of pigs fed the PC diet (Roux et al, 2011).…”
Section: Expmentioning
confidence: 99%
“…Also, Jin et al (2010) found an impairment of ADG and FCR with 30% of Lys restriction over a control diet containing 6 g total Lys/kg. Some authors have used the blood urea content to define Lys requirements (Roux et al, 2011), although not always successfully (Cameron et al, 2003), depending on the supply of non-limiting AAs relative to Lys. In the current study, the formulation of diets for similar content of ideal protein prevented the response of serum urea to dietary Lys.…”
Section: Discussionmentioning
confidence: 99%